الاقتصاد الدائري القائم على المعرفة كمدخل إبداعي للتنمية المستدامة - (:unkn) unknown (University of Eloued جامعة الوادي, 2019)
يعتبر الاقتصاد الدائري اقتصاد حيوي يهدف إلى تغيير الطريقة التي نعيش بها من خلال الاعتماد على الإبداع والتطوير والابتكار في الصناعة والاستهلاك وتوفير العديد من الفرص لضمان الاستدامة والنمو على المدى الطويل، وتساهم إدارة المعرفة باعتبارها مورداً أساسياً من الموارد الاقتصادية يتم إنتاجها والاستثمار فيها وتداولها بما يحقق النمو الاقتصادي، كونها عبارة عن رأس مال في حد ذاتها تقوم على الأفكار والخبرات والممارسات الأفضل، وهو ما يؤكد بأن حجم المساحة التي يمكن أن تشغلها إدارة المعرفة في الاقتصاد الدائري سيكون أكثر وأكبر عمقاً، لدورها بتقديم حلول إبداعية مبتكرة تسعى لخلق توازن بين تحقيق التنمية المستدامة وحماية البيئة مع الحفاظ على الموارد الطبيعية والحيلولة دون استنزافها وقدرتها على مواكبة التطورات التقنية المتسارعة والمستمرة بمختلف المجالات لتقديم قاعدة مدخلات للاقتصاد الدائري تطور الدورات العكسية وتزيد من فاعلية الموارد وفق تفكير جماعي هادف ومنظم يواكب التطور النوعي لتكنولوجيا المعلومات باتجاه Miniaturization, Speed, and Portability ويطرح رؤى مستقبلية متكاملة لإعادة تصميم سلاسل التوريد بهدف تقديم تشكيلة غير مسبوقة من منتجات وخدمات الاقتصاد الدائري القائم على المعرفة، والتي يعبر مدى توافرها عن المستوى التنموي الذي حققته الدول، بهدف إحداث تحول نوعي يمثل منهجاً مؤثراً ومتأثراً للوصول إلى تقديم علاقة متكاملة بين منهج الاقتصاد الدائري وإدارة المعرفة ويكون نموذجاً مثالياً من أجل تحقيق تنمية مستدامة Abstract: The circular economy is a vital economy that aims to change the way we live by relying on innovation, development and innovation in industry and consumption and providing many opportunities to ensure long-term sustainability and growth. Knowledge management contributes as an essential resource for economic resources produced, invested and traded to achieve growth. Economic, as it is a capital in itself based on ideas, experiences and best practices, which confirms that the size of space that can be occupied by knowledge management in the circular economy will be more and deeper, for its role in providing solutions Innovative innovation seeks to strike a balance between achieving sustainable development and protecting the environment while preserving natural resources and preventing its depletion and its ability to keep abreast of the rapid and continuous technological developments in various fields to provide an input base for the circular economy. The development of reverse cycles and increase the effectiveness of resources, Towards Miniaturization, Speed, and Portability, and provides a comprehensive future vision for redesigning supply chains to provide an unprecedented range of products and services for the knowledge-based circular economy, The level of development achieved by countries in order to achieve qualitative transformation is an influential and influential approach to achieve an integrated relationship between the circular economy approach and knowledge management and is an ideal model for achieving sustainable development.
The Circular Economy Based on Knowledge as an Innovative Approach to Sustainable Development
الملتقى الدولي الثامن حول: الاتجاهات الحديثة للتجارة الدولية وتحديات التنمية المستدامة نحو رؤى مستقبلية واعدة للدول النامية 02/ 03 ديسمبر 2019 - كلية العلوم الاقتصادية والتجارية وعلوم التسيير - جامعة الشهيد حمه لخضر - الوادي
Keywords: الاقتصاد الدائري، إدارة المعرفة، التنمية المستدامة; Circular economics, knowledge management, sustainable development